The Food Nutrient Index and Inflammation Are Not Linked to Eccentric Exercise-Induced Muscle Damage. (14th June 2022) - Nieman, David; Simonson, Andrew; Williams, Joshua; Arnold, Matthew; Arnett, Lathan; Blevins, Tondra; Valacchi, Giuseppe; Lila, Mary
Abstract: Objectives: Variation in muscle damage following eccentric exercise is wide-ranging and largely unexplained. This study investigated linkages between eccentric exercise-induced increases in the muscle damage biomarker creatine kinase (CK) and diet quality, body composition and fitness test performance, diagnostic chemistries, oxidative stress, and inflammation. Methods: Participants included 53 healthy, non-obese male (n = 30) and female adults (n = 23) (20–55 y, BMI < 30 kg/m 2 ) who were not engaged in regular resistance training. After familiarization, participants engaged in a 90-min bout of whole-body eccentric exercise (90-EE) (17 exercises). Changes in muscle soreness (DOMS, 1–10 scale) and damage biomarkers (serum CK, myoglobin), exercise performance, oxidative stress (4-hydroxynonenal or 4HNE), inflammation (CRP, IL-18, IL-16, IL-10), serum cortisol, and diagnostic chemistries were monitored immediately post-90-EE, and then each morning during a 4-d recovery period. Blood samples were collected in an overnight fasted state, with serum CK, myoglobin, cortisol, and diagnostic chemistries measured at a clinical lab. IL-18, IL-6, IL-10, and 4HNE were assayed by ELISA. Participants entered food and beverage intake in 3-d food records with nutrient and flavonoid intake assessed and the Food Nutrient Index (FNI) calculated using eight under-consumed nutrients. Results: The 90-EE bout induced significant DOMS and muscle damage, inflammation and oxidative stress, and decreases in strength and anaerobic power. CK increased throughout the 4-d recovery period, with the highest levels measured on the 4 th day (range, 60–17, 040 U/L; mean ± SD, 1, 565 ± 3, 132 U/L). CK was correlated with other tissue damage biomarkers including aspartate aminotransferase (r = 0.946), lactate dehydrogenase (r = 0.884), and myoglobin (r = 0.763). Under linear regression analysis with non-tissue damage outcomes including FNI (68.7 ± 15.7),  DOMS and serum cortisol emerged as the best predictors of post-90-EE CK variance [R 2  = 0.367, F(2, 50) = 14.48, p < 0.001]. Conclusions: The CK response to 90-EE varied widely between participants with 37% of the variance related to perceptions of muscle soreness and the stress hormone cortisol, but not diet quality, inflammation, oxidative stress, or fitness test performance. Funding Sources: MegaFood.